Analisis Peran Vegetasi Ruang Terbuka Hijau terhadap Kualitas Udara di Kawasan Permukiman Padat Kota Makassar - Hasanuddin Molo; Herlina Sattuang; Riska Wulandari; M. Yusuf; I Wayan Sudiyanto; Sri Magfirah HS; Rizki Amaliah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study aimed to analyze the role of green open space (GOS) vegetation on air quality in densely populated residential areas of Makassar City. Rapid urban development, increased vehicle activity, and the reduction of urban green spaces have contributed to the decline in environmental quality, particularly ambient air quality, in urban settlements. The research was conducted in the Tamalanrea District at six observation points representing commercial areas, main roads, warehouse areas, and residential settlements. A quantitative descriptive method was applied through direct field measurements of ambient air quality parameters, including Sulfur Dioxide (SO₂), Nitrogen Dioxide (NO₂), Carbon Monoxide (CO), Total Suspended Particulate (TSP), and Lead (Pb), combined with vegetation observations to identify vegetation density and dominant plant species at each observation point. The results showed that ambient air quality at all observation points remained below the national ambient air quality standards. Higher concentrations of SO₂, NO₂, and TSP were found in areas with high vehicle activity, such as commercial zones, residential gateways, and warehouse areas. In contrast, residential areas with denser vegetation cover tended to show lower concentrations of air pollutants. Vegetation in the study area was dominated by species such as Samanea saman, Swietenia mahagoni, Tabebuia sp., Terminalia mantaly, and Syzygium oleina. The findings indicate that vegetation density and land-use characteristics influence ambient air quality conditions in urban residential areas. Therefore, the development and preservation of green open spaces are essential to support environmental sustainability and improve urban air quality.